Respuesta :
Answer:
[tex]\displaystyle \int\limits^{0}_{- \infty} {\frac{1}{(x - 1)^2}} \, dx = 1[/tex]
General Formulas and Concepts:
Calculus
Limits
- Limit Rule [Variable Direct Substitution]: [tex]\displaystyle \lim_{x \to c} x = c[/tex]
Differentiation
- Derivatives
- Derivative Notation
Derivative Property [Addition/Subtraction]: [tex]\displaystyle \frac{d}{dx}[f(x) + g(x)] = \frac{d}{dx}[f(x)] + \frac{d}{dx}[g(x)][/tex]
Basic Power Rule:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Integration
- Integrals
- Improper Integrals
Integration Rule [Reverse Power Rule]: [tex]\displaystyle \int {x^n} \, dx = \frac{x^{n + 1}}{n + 1} + C[/tex]
Integration Rule [Fundamental Theorem of Calculus 1]: [tex]\displaystyle \int\limits^b_a {f(x)} \, dx = F(b) - F(a)[/tex]
U-Substitution
Area of a Region Formula: [tex]\displaystyle A = \int\limits^b_a {[f(x) - g(x)]} \, dx[/tex]
Step-by-step explanation:
Step 1: Define
[tex]\displaystyle f(x) = \frac{1}{(x - 1)^2} \\\left[ -\infty ,\ 0 \right][/tex]
Step 2: Integrate Pt. 1
- Substitute in variables [Area of a Region Formula]: [tex]\displaystyle \int\limits^{0}_{- \infty} {\frac{1}{(x - 1)^2}} \, dx[/tex]
- [Integral] Rewrite [Improper Integral]: [tex]\displaystyle \int\limits^{0}_{- \infty} {\frac{1}{(x - 1)^2}} \, dx = \lim_{a \to -\infty} \int\limits^{0}_{a} {\frac{1}{(x - 1)^2}} \, dx[/tex]
Step 3: Integrate Pt. 2
Identify variables for u-substitution.
- Set u: [tex]\dipslaystyle u = x - 1[/tex]
- [u] Basic Power Rule [Derivative Property - Addition/Subtraction]: [tex]\dipslaystyle du = dx[/tex]
- [Limits] Switch: [tex]\displaystyle \left \{ {{x = 0 ,\ u = 0 - 1 = -1} \atop {x = a ,\ u = a - 1}} \right.[/tex]
Step 4: Integrate Pt. 3
- [Integral] U-Substitution: [tex]\displaystyle \int\limits^{0}_{- \infty} {\frac{1}{(x - 1)^2}} \, dx = \lim_{a \to -\infty} \int\limits^{-1}_{a - 1} {\frac{1}{u^2}} \, du[/tex]
- [Integral] Integration Rule [Reverse Power Rule]: [tex]\displaystyle \int\limits^{0}_{- \infty} {\frac{1}{(x - 1)^2}} \, dx = \lim_{a \to -\infty} \frac{-1}{x} \bigg| \limits^{-1}_{a - 1}[/tex]
- Evaluate [Integration Rule - Fundamental Theorem of Calculus 1]: [tex]\displaystyle \int\limits^{0}_{- \infty} {\frac{1}{(x - 1)^2}} \, dx = \lim_{a \to -\infty} \bigg( \frac{1}{a - 1} + 1 \bigg)[/tex]
- Evaluate limit [Limit Rule - Variable Direct Substitution]: [tex]\displaystyle \int\limits^{0}_{- \infty} {\frac{1}{(x - 1)^2}} \, dx = 0 + 1[/tex]
- Simplify: [tex]\displaystyle \int\limits^{0}_{- \infty} {\frac{1}{(x - 1)^2}} \, dx = 1[/tex]
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Advanced Integration Techniques